Scratch-resistant water-based paint as well as preparation method and application thereof

By adding silica, alumina and silicon carbide powder of specific particle sizes to the aqueous coating, combined with aqueous polyurethane acrylate resin and photoinitiator, the problems of difficulty in operating and poor texture in automotive leather are solved. It significantly improves scratch resistance and stability, and improves the user experience and appearance quality of automotive leather.

CN119144223AActive Publication Date: 2024-12-17QINGYUAN MELESI ENVIRONMENTAL PROTECTION NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411381007.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-17
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Existing water-based coatings have problems such as difficulty in operation, insufficient low temperature flexibility and poor texture in automotive leather, which affects its scratch resistance and user experience.

Method used

By adding specific particle sizes and amounts of silica, alumina and silicon carbide powder to the aqueous coating, combining aqueous polyurethane acrylate resin and photoinitiator, a high-performance scratch-resistant coating is formed to improve the stability and flexibility of the coating. and scratch resistance.

Benefits of technology

It significantly improves the scratch resistance, stability and flexibility of water-based coatings, improves the user experience and appearance quality of automotive leather, and enhances the hardness, wear resistance and anti-aging properties of the coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005069904640000071
    Figure BDA0005069904640000071
  • Figure BDA0005069904640000081
    Figure BDA0005069904640000081
Patent Text Reader

Abstract

The invention belongs to the technical field of waterborne coatings for leather, and discloses a scratch-resistant waterborne coating and a preparation method and application thereof.The scratch-resistant waterborne coating is prepared from, by weight, 80-110 parts of waterborne polyurethane acrylate resin, 0.5-1 part of silicon dioxide, 6-10 parts of aluminum oxide, 0.1-1 part of silicon carbide micro powder, 0.1-0.3 part of a stabilizer, 0.3-0.6 part of a flatting agent and 0.3-0.6 part of a defoaming agent; wherein the particle size of the silicon dioxide is 20-40 nm; the aluminum oxide is divided into first aluminum oxide and second aluminum oxide, the weight ratio of the first aluminum oxide to the second aluminum oxide is (2-3): (7-8), the particle size of the first aluminum oxide is 70-80 nm, and the particle size of the second aluminum oxide is 10-15 nm; the particle size of the silicon carbide micro powder is 10-15 nm. According to the invention, on the basis that the second aluminum oxide with a smaller particle size is compounded with the first aluminum oxide, the silicon carbide micro powder with the same particle size as the second aluminum oxide is added and the silicon dioxide with a specific particle size is compounded, so that the effect of synergistically improving the scratch resistance of the water-based paint can be generated, and the scratch resistance of the water-based paint is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water-based coatings for leather, and in particular to a scratch-resistant water-based coating, a preparation method and uses thereof. Background Art

[0002] Water-based coatings for automotive leather mainly include water-based leather paint and water-based polyurethane leather brightener. These products are widely used in the field of automotive interiors due to their environmental protection, safety, and excellent mechanical properties.

[0003] Since automotive interior leather is exposed to a variety of situations that may cause scratches during daily use, including friction from clothing, dragging of luggage, hand touch and even accidental collisions, these factors may damage the leather surface, affecting its appearance and durability. Therefore, the scratch resistance of water-based coatings is a very important product performance requirement for automotive leather.

[0004] Prior art 1: Chinese patent application 202110004799.1 discloses a wear-resistant and scratch-resistant water-based synthetic leather polyurethane resin and a preparation method thereof, comprising the following substances in parts by weight: 160-240 parts of polymer diol, 56-100 parts of polydiisocyanate, 7.2-13.2 parts of carboxylic acid type small molecule diol, 6-10 parts of hydroxyl type small molecule diol, 0.2-0.4 parts of catalyst, 80-140 parts of acetone, 7-12 parts of sulfonate type diol, 4.1-6.8 parts of neutralizer, 550-820 parts of deionized water, 4-8 parts of cross-linking modifier, 4-6 parts of wetting agent, and 4-6 parts of leveling agent.

[0005] Prior art 1 uses polycarbonate diol and adds polysiloxane-modified polyurethane resin to improve the water resistance, acid and alkali resistance, and surface smoothness of the resin coating, thereby improving its scratch resistance. Compared with ordinary polyether diols, the wear resistance of polycarbonate diol is greatly improved, and triamine cross-linking modification is used to achieve network cross-linking of the molecular structure, thereby improving the wear and scratch resistance of the resin coating.

[0006] However, since polycarbonate diol is a crystal, it is difficult to operate when used in the preparation of water-based coatings, which increases the difficulty of production. It also lacks flexibility at low temperatures and has a poor texture. When used for automotive leather, it will reduce the user experience and appearance of the automotive leather, and is not very suitable for automotive leather.

[0007] Based on this, developing water-based coatings with high scratch resistance suitable for automotive leather is currently a research and development hotspot. Summary of the invention

[0008] One of the purposes of the present invention is to provide a scratch-resistant water-based coating, which effectively improves the stability, flexibility and scratch resistance of the water-based coating by adding silicon dioxide, aluminum oxide and silicon carbide micropowders with specific particle sizes and specific amounts, and has excellent texture when used for automotive leather.

[0009] Another object of the present invention is to provide a method for preparing a scratch-resistant water-based coating, wherein the prepared scratch-resistant water-based coating has excellent scratch resistance, stability, flexibility and other properties.

[0010] At the same time, the present invention also provides an application of a scratch-resistant water-based coating, which, when used as a coating for automotive leather, can provide the automotive leather with excellent scratch resistance, flexibility and texture, thereby improving the user experience of the automotive leather.

[0011] To achieve the above object, the present invention provides a scratch-resistant water-based coating, which comprises, by weight, 80-110 parts of water-based polyurethane acrylate resin, 0.5-1 parts of silicon dioxide, 6-10 parts of aluminum oxide, 0.1-1 parts of silicon carbide powder, 0.1-0.3 parts of stabilizer, 0.3-0.6 parts of leveling agent, and 0.3-0.6 parts of defoamer;

[0012] The particle size of the silicon dioxide is 20-40 nm;

[0013] The alumina is divided into a first alumina and a second alumina, the weight ratio of the first alumina to the second alumina is 2-3:7-8, the particle size of the first alumina is 70-80 nm, and the particle size of the second alumina is 10-15 nm;

[0014] The particle size of the silicon carbide powder is 10-15 nm.

[0015] Nano-scale silica can effectively improve the UV absorption capacity of water-based coatings, and can effectively improve the smoothness, anti-aging performance, self-cleaning performance, etc. of water-based coatings, and it can also improve the hardness, wear resistance, scratch resistance and weather resistance of coatings;

[0016] The addition of alumina will also improve the performance of water-based coatings. As a high-performance filler, its addition to water-based coatings can significantly improve the performance of the coatings. Specifically, the high hardness, high purity, and high transparency of alumina enable it to:

[0017] (1) Improve scratch resistance: The addition of aluminum oxide can significantly improve the scratch resistance of the product, making the paint film stronger and more resistant to external friction and wear.

[0018] (2) Enhanced wear resistance: The addition of aluminum oxide can greatly improve the wear resistance of the paint, making it more resistant to wear and reducing peeling and shedding during use.

[0019] (3) Improve hardness: By improving the structure of the paint, aluminum oxide helps to increase the hardness of the paint film, thereby enhancing the durability of the paint.

[0020] (4) Maintaining basic properties: Alumina has good dispersibility and will not chemically react with other material components when added to the coating, so it will not affect the basic properties of the material and the performance of other additives.

[0021] (5) Improve product performance: The addition of alumina helps improve the product's chemical resistance, high gloss and other properties while maintaining the basic properties of the coating unchanged.

[0022] (6) In addition, alumina can improve the fluidity of the coating, reduce viscosity, increase the solid content of the coating, and reduce the use of volatile organic compounds, thus contributing to environmental protection.

[0023] The choice of alumina particle size will affect the quality of automotive leather. The larger the particle size of alumina, the more obvious the improvement in the hardness, wear resistance and scratch resistance of water-based coatings. However, alumina with large particle size will affect the texture of automotive leather, and alumina with too small particle size will greatly reduce the improvement in the hardness, wear resistance and scratch resistance of water-based coatings.

[0024] In order to enable the water-based paint to maintain or even improve the user experience of automotive leather, the present invention only uses a small amount of first aluminum oxide with a larger particle size to improve the scratch resistance and wear resistance of the water-based paint. At the same time, the present invention also finds that on the basis of using a second aluminum oxide with a smaller particle size to compound the first aluminum oxide, by adding silicon carbide micropowder with the same particle size as the second aluminum oxide and compounding it with silicon dioxide with a specific particle size, the scratch resistance of the water-based paint can be synergistically improved.

[0025] Preferably, the stabilizer comprises an ultraviolet absorber and a light stabilizer, and the weight ratio of the ultraviolet absorber to the light stabilizer is 1-10:1-10.

[0026] More preferably, the weight ratio of the ultraviolet absorber to the light stabilizer is 1:4.

[0027] Preferably, the light stabilizer is a hindered amine light stabilizer.

[0028] Preferably, the ultraviolet absorber is one of ultraviolet absorber UV-9, ultraviolet absorber UV-531, and ultraviolet absorber UVP-327.

[0029] Preferably, the leveling agent is leveling agent SN4034.

[0030] Preferably, the defoaming agent is SN-6725.

[0031] Furthermore, the waterborne polyurethane acrylate resin in the scratch-resistant waterborne coating is a UV light-cured waterborne polyurethane acrylate resin, and accordingly, the scratch-resistant waterborne coating further comprises 1 to 4 parts of a photoinitiator.

[0032] Preferably, the photoinitiator is at least one of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxy-cyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl diphenyl phosphine oxide.

[0033] The present invention also provides a method for preparing a scratch-resistant water-based coating, comprising the following steps:

[0034] Step 1: mixing silicon dioxide, a first aluminum oxide, a second aluminum oxide and silicon carbide micropowder to obtain a mixed powder, and then adding an appropriate amount of a dispersant and deionized water to the mixed powder for grinding and dispersion to obtain a dispersed mixed powder;

[0035] Step 2: The remaining components and the dispersed mixed powder are mixed and stirred evenly to obtain a scratch-resistant water-based coating.

[0036] The dispersant is at least one of polyethylene glycol and sodium lauryl sulfate, and the amount of the dispersant is 2-5% of the mixed powder.

[0037] Specifically, the preparation method of the scratch-resistant water-based coating is:

[0038] Step 1: mixing silicon dioxide, a first aluminum oxide, a second aluminum oxide and silicon carbide micropowder to obtain a mixed powder, and then adding an appropriate amount of a dispersant and deionized water to the mixed powder for grinding and dispersion to obtain a dispersed mixed powder;

[0039] Step 2: Homogenize and stir the waterborne polyurethane acrylate resin, stabilizer, leveling agent, defoamer, photoinitiator and the dispersed mixed powder.

[0040] It should be noted that step 1 of the present invention is intended to fully disperse the nano-scale powder, so the amount of deionized water used is based on the prior art and is not particularly limited.

[0041] Preferably, the waterborne polyurethane acrylate resin may be commercially available waterborne polyurethane acrylate resin.

[0042] The present invention also provides an application of the scratch-resistant water-based paint, wherein the scratch-resistant water-based paint is used as a coating for automotive leather.

[0043] Beneficial Effects

[0044] Compared with the prior art, the present invention has at least the following advantages:

[0045] (1) The present invention uses silicon dioxide to modify waterborne polyurethane acrylate resin, which can effectively improve the smoothness, anti-aging performance, self-cleaning performance, etc. of the waterborne coating, and improve the hardness, wear resistance, scratch resistance and weather resistance of the coating;

[0046] (2) The present invention uses aluminum oxide to modify the waterborne polyurethane acrylate resin, which can effectively improve the scratch resistance, wear resistance, hardness and other properties of the waterborne coating;

[0047] (3) The present invention ensures that the aluminum oxide can improve the scratch resistance of the water-based coating while avoiding the problem that the texture and use experience of the automotive leather are significantly reduced due to the excessive particle size of the aluminum oxide by compounding the first aluminum oxide with the second aluminum oxide with the smaller particle size;

[0048] (4) Since the amount of the first alumina with a larger particle size is small, the improvement of the scratch resistance of the water-based coating by the composite of the first alumina and the second alumina is relatively limited. The present invention uses the second alumina with a smaller particle size to composite the first alumina. By adding silicon carbide micropowder with the same particle size as the second alumina and compounding it with silicon dioxide with a specific particle size, it can produce a synergistic effect of improving the scratch resistance of the water-based coating, thereby significantly improving the scratch resistance of the water-based coating. DETAILED DESCRIPTION

[0049] The present invention will be further described below in conjunction with the embodiments, but it does not constitute any limitation to the present invention. Any limited number of modifications made within the scope of the claims of the present invention are still within the scope of the claims of the present invention.

[0050] In order to explain the technical content of the present invention in detail, further description is given below in conjunction with the implementation modes.

[0051] In the following examples and comparative examples, the waterborne polyurethane acrylate resin is purchased from the waterborne UV resin DR-W470 provided by Hubei Langbowan Biomedicine Co., Ltd., the hindered amine light stabilizer is purchased from the TINUVIN 783FDL long-term heat stabilizer provided by Shanghai Jingyan Chemical Co., Ltd., the ultraviolet absorber UV-531 is purchased from Dongguan Xingyuan Chemical Co., Ltd., the leveling agent SN4034 and the defoamer SN-6725 are both purchased from Shanghai Shenzhu Chemical Technology Co., Ltd., and the photoinitiator is purchased from 2-hydroxy-2-methyl-1-phenyl-1-propanone provided by Shandong Xinghai Chemical Co., Ltd.

[0052] It should be noted that the technical solution of the present invention can be implemented through other commercially available products and is not limited to the above-mentioned manufacturers.

[0053] In the following examples and comparative examples, the particle sizes of the silicon dioxide powder, the first aluminum oxide powder, the second aluminum oxide powder and the silicon carbide powder are all obtained by sieving, which belongs to the prior art and the specific steps are not described in detail.

[0054] Unless otherwise specified, % and part in the present invention refer to percent by weight and part by weight.

[0055] The following examples and comparative examples all adopt the following steps to prepare water-based coatings:

[0056] Step 1: mixing silicon dioxide, a first aluminum oxide, a second aluminum oxide and silicon carbide micropowder to obtain a mixed powder, and then adding an appropriate amount of a dispersant and deionized water to the mixed powder for grinding and dispersion to obtain a dispersed mixed powder;

[0057] Step 2: Homogenize and stir the remaining components with the dispersed mixed powder.

[0058] Example 1

[0059] A scratch-resistant water-based coating comprises 80 parts of water-based polyurethane acrylate resin, 0.6 parts of silicon dioxide powder with a particle size of 20-40 nm, 1.2 parts of a first aluminum oxide powder with a particle size of 70-80 nm, 4.8 parts of a second aluminum oxide powder with a particle size of 10-15 nm, 0.3 parts of silicon carbide micropowder with a particle size of 10-15 nm, 0.02 parts of a hindered amine light stabilizer, 0.08 parts of an ultraviolet absorber UV-531, 0.4 parts of a leveling agent, 0.3 parts of a defoaming agent, and 3 parts of a photoinitiator.

[0061] Example 2

[0062] A scratch-resistant water-based coating comprises 110 parts of water-based polyurethane acrylate resin, 1 part of silicon dioxide powder with a particle size of 20-40 nm, 3 parts of first aluminum oxide powder with a particle size of 70-80 nm, 7 parts of second aluminum oxide powder with a particle size of 10-15 nm, 1 part of silicon carbide micropowder with a particle size of 10-15 nm, 0.02 parts of hindered amine light stabilizer, 0.08 parts of ultraviolet absorber UV-531, 0.4 parts of leveling agent, 0.3 parts of defoaming agent and 3 parts of photoinitiator.

[0063] Example 3

[0064] A scratch-resistant water-based coating comprises 95 parts of water-based polyurethane acrylate resin, 0.6 parts of silicon dioxide powder with a particle size of 20-40 nm, 1.6 parts of a first aluminum oxide powder with a particle size of 70-80 nm, 6.4 parts of a second aluminum oxide powder with a particle size of 10-15 nm, 0.8 parts of silicon carbide micropowder with a particle size of 10-15 nm, 0.02 parts of a hindered amine light stabilizer, 0.08 parts of an ultraviolet absorber UV-531, 0.4 parts of a leveling agent, 0.3 parts of a defoaming agent, and 3 parts of a photoinitiator.

[0065] Comparative Example 1

[0066] A scratch-resistant water-based coating comprises 95 parts of water-based polyurethane acrylate resin, 0.6 parts of silicon dioxide powder with a particle size of 20-40 nm, 1.6 parts of a first aluminum oxide powder with a particle size of 70-80 nm, 6.4 parts of a second aluminum oxide powder with a particle size of 10-15 nm, 0.02 parts of a hindered amine light stabilizer, 0.08 parts of an ultraviolet absorber UV-531, 0.4 parts of a leveling agent, 0.3 parts of a defoaming agent, and 3 parts of a photoinitiator.

[0067] Comparative Example 2

[0068] A scratch-resistant water-based coating comprises 95 parts of water-based polyurethane acrylate resin, 0.6 parts of silicon dioxide powder with a particle size of 20-40 nm, 1.6 parts of a first aluminum oxide powder with a particle size of 70-80 nm, 7.2 parts of a second aluminum oxide powder with a particle size of 10-15 nm, 0.02 parts of a hindered amine light stabilizer, 0.08 parts of an ultraviolet absorber UV-531, 0.4 parts of a leveling agent, 0.3 parts of a defoaming agent, and 3 parts of a photoinitiator.

[0069] Comparative Example 3

[0070] It is generally the same as Example 3, except that the particle size of the second aluminum oxide is 20-40 nm.

[0071] Comparative Example 4

[0072] It is generally the same as Example 3, except that the particle size of the first aluminum oxide is 20-40 nm.

[0073] Comparative Example 5

[0074] It is generally the same as Example 3, except that the particle size of the first aluminum oxide is 10-15 nm.

[0075] Comparative Example 6

[0076] It is generally the same as Example 3, except that the particle size of the silicon carbide powder is 20-40 nm.

[0077] Comparative Example 7

[0078] It is generally the same as Example 3, except that the particle size of the silicon carbide powder is 3-8 nm.

[0079] Comparative Example 8

[0080] It is generally the same as Example 3, except that the particle size of the second aluminum oxide is 3-8 nm.

[0081] Performance Testing

[0082] The water-based coatings obtained in Examples 1-3 and Comparative Examples 1-8 were sprayed on PVC artificial leather and cured, respectively. Then, a five-finger scratch tester was used to rub the surface of the PVC artificial leather back and forth once under pressure conditions of 10N, 12N, 15N, and 20N, respectively. Each test was performed on a new piece of PVC artificial leather sprayed and cured with the water-based coating. The surfaces of the PVC artificial leather sprayed with the water-based coatings obtained in Examples 1-3 and Comparative Examples 1-8 were observed to see whether there was damage or color difference. The results are shown in Table 1.

[0083] It should be noted that if the PVC artificial leather is damaged when tested under low pressure conditions, no testing under higher pressure conditions will be performed.

[0084] Table 1 Scratch resistance results of water-based coatings obtained in Examples 1-3 and Comparative Examples 1-8

[0085]

[0086]

[0087] According to the results in Table 1, we can see that:

[0088] According to the data of Examples 1-3, the present invention can effectively improve the scratch resistance of water-based coatings by compounding silicon dioxide with specific particle sizes, first aluminum oxide, second aluminum oxide and silicon carbide powder.

[0089] According to the data comparison between Example 3 and Comparative Examples 1 and 2, it can be seen that the scratch resistance of the water-based coating in Comparative Examples 1 and 2 is greatly reduced without adding silicon carbide powder. In Comparative Example 2, silicon carbide powder is added to the second alumina, but its scratch resistance is not significantly improved compared with Comparative Example 1. The reason is that the second alumina powder with a small particle size has a very limited effect on improving the scratch resistance of the water-based coating, and the addition of a small amount cannot effectively improve the scratch resistance of the water-based coating. It can be seen that the addition of silicon carbide powder in the present invention is particularly critical, and it can synergistically improve the scratch resistance of the water-based coating with silicon dioxide, the first alumina, and the second alumina.

[0090] According to the data comparison between Example 3 and Comparative Examples 3, 6, 7 and 8, although Comparative Example 3 increases the particle size of the second aluminum oxide, the scratch resistance of the water-based coating is reduced. Similarly, Comparative Example 7 reduces the particle size of the silicon carbide micropowder. In theory, the smaller the particle size of the silicon carbide micropowder, the better the performance optimization of the water-based coating. However, Comparative Examples 3 and 7 respectively use the second aluminum oxide and silicon carbide micropowder, which theoretically improve the scratch resistance of the water-based coating, but the scratch resistance of the water-based coating is reduced. It is speculated that the possible reason is that the present invention adds silicon carbide micropowder with the same particle size range as the second aluminum oxide, and during the curing and molding process of the water-based coating, the silicon dioxide, the first aluminum oxide and the second aluminum oxide are added. Aluminum dioxide forms a specific structure, and in the process, silicon carbide powder replaces part of the structural position of the second aluminum oxide, thereby forming a new structure, which synergistically improves the scratch resistance of the water-based coating, greatly improving the scratch resistance of the water-based coating; Comparative Examples 3 and 7 make the particle sizes of the second aluminum oxide and silicon carbide powder different, which makes it difficult for silicon carbide powder to replace part of the second aluminum oxide to produce a new stable structure; similarly, Comparative Examples 6 and 8 also lead to the same results, and because the particle size selection of silicon carbide powder and the particle size selection of the second aluminum oxide are worse, the simple component efficacy superposition effect produced by Comparative Examples 6 and 8 is worse, and the scratch resistance of their water-based coatings is lower than that of Comparative Examples 3 and 7.

[0091] According to the data comparison between Example 3 and Comparative Examples 4 and 5, it can be seen that the particle size selection of the first aluminum oxide will also seriously affect the scratch resistance performance of the water-based coating. The possible reason is speculated to be: in the technical scheme of the present invention, a first aluminum oxide and silicon dioxide are used as the basis, and then a second aluminum oxide and silicon carbide powder are compounded to form a stable structure, thereby synergistically improving the scratch resistance of the water-based coating.

[0092] The embodiments presented herein are only embodiments selected according to the combination of all possible embodiments. The appended claims should not be limited by the embodiments describing the present invention. Some numerical ranges used in the claims include sub-ranges therein, and the changes in these ranges should also be covered by the appended claims.

Claims

1. A scratch-resistant water-based coating, characterized in that: In parts by weight, it comprises 80-110 parts of waterborne polyurethane acrylate resin, 0.5-1 parts of silicon dioxide, 6-10 parts of aluminum oxide, 0.1-1 parts of silicon carbide micropowder, 0.1-0.3 parts of stabilizer, 0.3-0.6 parts of leveling agent, and 0.3-0.6 parts of defoamer; The particle size of the silicon dioxide is 20-40 nm; The alumina is divided into a first alumina and a second alumina, the weight ratio of the first alumina to the second alumina is 2-3:7-8, the particle size of the first alumina is 70-80 nm, and the particle size of the second alumina is 10-15 nm; The particle size of the silicon carbide powder is 10-15 nm.

2. The scratch-resistant water-based coating according to claim 1, characterized in that: The stabilizer includes an ultraviolet absorber and a light stabilizer, and the weight ratio of the ultraviolet absorber to the light stabilizer is 1-10:1-10.

3. The scratch-resistant water-based coating according to claim 2, characterized in that: The light stabilizer is a hindered amine light stabilizer.

4. The scratch-resistant water-based coating according to claim 2, characterized in that: The ultraviolet absorber is one of ultraviolet absorber UV-9, ultraviolet absorber UV-531 and ultraviolet absorber UVP-327.

5. The scratch-resistant water-based coating according to claim 1, characterized in that: Also includes 1-4 parts of photoinitiator.

6. A method for preparing a scratch-resistant water-based coating according to any one of claims 1 to 5, characterized in that: The steps include: Step 1: mixing silicon dioxide, a first aluminum oxide, a second aluminum oxide and silicon carbide micropowder to obtain a mixed powder, and then adding an appropriate amount of a dispersant and deionized water to the mixed powder for grinding and dispersion to obtain a dispersed mixed powder; Step 2: The remaining components and the dispersed mixed powder are mixed and stirred evenly to obtain a scratch-resistant water-based coating.

7. An application of the scratch-resistant water-based coating according to any one of claims 1 to 5, characterized in that: The scratch-resistant water-based paint is used as a coating for automotive leather.

Citation Information

Patent Citations

  • Wear-resistant high-strength coating and preparation method thereof

    CN112760030A

  • Silicon carbide wear-resistant coating for repairing and protecting flow passage component

    CN114437619A

  • Enhanced scratch resistant coatings using inorganic fillers

    US20030092789A1

  • Wear-resistant powder-loading layer coating, wear-resistant layer, and preparation method therefor and use thereof

    WO2017121399A1

Cited By

  • Waterproof and breathable coating for leather and preparation method of waterproof and breathable coating

    CN119799142A